2019
DOI: 10.3114/fuse.2019.04.06
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and multi-locus phylogeny of cylindrocarpon-like species associated with diseased roots of grapevine and other fruit and nut crops in California

Abstract: Black foot disease is a common and destructive root disease of grapevine caused by a multitude of cylindrocarponlike fungi in many viticultural areas of the world. This study identified 12 cylindrocarpon-like fungal species across five genera associated with black foot disease of grapevine and other diverse root diseases of fruit and nut crops in the Central Valley Region of California. Morphological observations paired with multi-locus sequence typing of four loci, internal transcribed spacer region of nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 42 publications
3
30
0
3
Order By: Relevance
“…With the four sets of primers used, we have achieved our goal of showing the spectrum of different species involved in the development of RRD symptoms, even in a single plant. Similar to our studies, Lawrence et al 67 identified, in a multi-locus sequence typing of four loci (ITS, TUB2, TEF1, and HIS), 12 Cylindrocarpon -like fungal species across five genera associated with black foot disease of grapevine and other diverse root diseases of fruit and nut crops in California. They stated that the HIS marker was essential, either singly or in combination with the other mentioned genes, for the precise identification of most Dactylonectria species.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…With the four sets of primers used, we have achieved our goal of showing the spectrum of different species involved in the development of RRD symptoms, even in a single plant. Similar to our studies, Lawrence et al 67 identified, in a multi-locus sequence typing of four loci (ITS, TUB2, TEF1, and HIS), 12 Cylindrocarpon -like fungal species across five genera associated with black foot disease of grapevine and other diverse root diseases of fruit and nut crops in California. They stated that the HIS marker was essential, either singly or in combination with the other mentioned genes, for the precise identification of most Dactylonectria species.…”
Section: Discussionsupporting
confidence: 88%
“…were also determined to be main causative pathogens of Rosaceous small fruit root diseases 17 and of the decline and root rot of loquat ( Eriobotrya japonica ‘Algerie’) 15 . Furthermore, Cylindrocarpon -like species have been described in connection with root rot and decline effects in kiwifruit ( Actinidia chienensis ), avocado ( Persea americana ), olive ( Olea europaea ), walnut ( Juglans regia ), and grapevine ( Vitis vinifera ) 67 . This underlines the wide host spectrum of these pathogenic Nectriaceae, which goes beyond the Rosaceae.…”
Section: Discussionmentioning
confidence: 99%
“…Many novel Ilyonectria and Ilyonectria-like species have been discovered recently (Carlucci et al, 2017;Lawrence et al, 2019). Due to the slow growth of some fungi, it is not easy to obtain species using separation techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 32 species of the genera Campylocarpon , Cylindrocladiella , Dactylonectria , Ilyonectria , Neonectria , Pleiocarpon and Thelonectria have been reported to cause black‐foot disease, 1,6–8 Dactyonectria torresensis is the most prevalent species associated with diseased vines in Europe 9–11 . These fungal species are known to be soilborne and persist as mycelium and conidia in rotten root fragments or as resting spores (chlamydospores) that can survive in the soil for extended periods of time after infected plants are removed 4,12 .…”
Section: Introductionmentioning
confidence: 99%